2020
DOI: 10.25011/cim.v43i3.34393
|View full text |Cite
|
Sign up to set email alerts
|

KIF4A: A potential biomarker for prediction and prognostic of prostate cancer

Abstract: Purpose: To investigate the clinical relevance and biological function of the kinesin super-family protein 4A (KIF4A) expression in prostate cancer (PCa). Methods: We examined 1) the relationship between the expression of KIF4A and clinico-pathological characteristics of PCa patients using a tissue microarray and the Cancer Genome Atlas database, 2) the prognostic value of KIF4A expression in patients using Kaplan-Meier plots and 3) the functions of KIF4A in LNCaP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Kinesin superfamily 4 (kinesin family member 4, KIF4), a kind of interaction with microtubules, which also provides power for components in the cell movement of motor, which can make the microtubules to the cells at the pole movement, has many physiological functions 6,7 . KIF4A spinning cone in the late adjustment form and plays a key role in the process of mitosis; the anomaly can lead to abnormal mitosis checkpoint and DNA damage repair, and chromosome instability and the formation of aneuploidy, cause abnormal cell proliferation, differentiation and cause tumor formation 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Kinesin superfamily 4 (kinesin family member 4, KIF4), a kind of interaction with microtubules, which also provides power for components in the cell movement of motor, which can make the microtubules to the cells at the pole movement, has many physiological functions 6,7 . KIF4A spinning cone in the late adjustment form and plays a key role in the process of mitosis; the anomaly can lead to abnormal mitosis checkpoint and DNA damage repair, and chromosome instability and the formation of aneuploidy, cause abnormal cell proliferation, differentiation and cause tumor formation 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ic50 concentration of WZ-3146 (1nM) on glioma was used to detect the effect of WZ-3146 on HUVEC cells, the MTT results indicated that the HUVEC cell activity could not be effected by WZ-3146 at 1nM relative to control group, suggesting WZ-3146 had a specific inhibitory effect on glioma. To further explore the possible pathways affected by WZ-3146 in glioma, we analyzed the effects of KIF4A on glioma signaling pathways by GSEA and found that KIF4A significantly affects the apoptosis signaling pathway in glioma, consistent with the finding that KIF4A knockdown can induce prostate and ovarian cancer cell apoptosis [ 33 , 34 ]. Therefore, we further examined the effect of WZ-3146 on glioma cell apoptosis, and the results confirmed that WZ-3146 can significantly induce glioma cell apoptosis, which further confirmed that WZ-3146 can limit glioma progression by targeting KIF4A.…”
Section: Discussionmentioning
confidence: 56%
“…KIF4A is involved in multiple cellular activities, particularly spindle formation and centrosome assembly in mitosis, chromosome concentration and separation, and DNA damage repair [ 17 ]. In addition, KIF4A is overexpressed in a variety of tumors [ 18 ]. A study on breast cancer established that ATAD2 could be recruited to the KIF4A promoter region by estrogen receptors alpha (ER α ) and other transcription factors to increase the transcription of KIF4A [ 19 ].…”
Section: Introductionmentioning
confidence: 99%